Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1128/mcb.24.1.1-13.2004
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Cholesterol Homeostasis in a Peroxisome-Deficient PEX2 Knockout Mouse Model

Abstract: We evaluated the major pathways of cholesterol regulation in the peroxisome-deficient PEX2 ؊/؊ mouse, a model for Zellweger syndrome. Zellweger syndrome is a lethal inherited disorder characterized by severe defects in peroxisome biogenesis and peroxisomal protein import. Compared with wild-type mice, PEX2 ؊/؊ mice have decreased total and high-density lipoprotein cholesterol levels in plasma. Hepatic expression of the SREBP-2 gene is increased 2.5-fold in PEX2 ؊/؊ mice and is associated with increased activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
81
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(92 citation statements)
references
References 62 publications
9
81
2
Order By: Relevance
“…In particular, peroxisomes seem to be necessary for the maintenance of the integrity of the inner mitochondrial membrane, a finding that confirms previous observations in patients 4,[6][7][8][9] and other mouse models. 13,36,37 Some of the presently observed ultrastructural changes at the inner mitochondrial membrane were similar to the alterations in Zellweger patients. However, crystalline inclusions in mitochondria were not seen in the livers of L-Pex5 knockout mice.…”
Section: Discussionsupporting
confidence: 48%
“…In particular, peroxisomes seem to be necessary for the maintenance of the integrity of the inner mitochondrial membrane, a finding that confirms previous observations in patients 4,[6][7][8][9] and other mouse models. 13,36,37 Some of the presently observed ultrastructural changes at the inner mitochondrial membrane were similar to the alterations in Zellweger patients. However, crystalline inclusions in mitochondria were not seen in the livers of L-Pex5 knockout mice.…”
Section: Discussionsupporting
confidence: 48%
“…9). This could not be explained by biosynthesis because: (1) expression of the classic pathway CYP7A1 gene is reduced 0.5-fold in early postnatal untreated mutants 9 and remains strongly suppressed in all P36 mutants, and (2) bile acid synthesis genes are down-regulated by bile acid treatment in PEX2 Ϫ/Ϫ mice (P. Faust, manuscript in preparation). Rather, our study showed that changes in basolateral bile acid transporter expressions, including decreased Ntcp, increased Mrp3, and decreased/absent Oatps, acted to exclude bile acids and their conjugates from PEX2 Ϫ/Ϫ hepatocytes, requiring excretion from alternate renal pathways 29 that may also be limiting.…”
Section: Discussionmentioning
confidence: 99%
“…5 Control mice had either PEX2 ϩ/ϩ or ϩ/Ϫ genotypes as biochemical and morphologic measures did not differ. 8,9 All protocols for animal use and experiments were reviewed and approved by the Institutional Animal Care and Use Committee of Columbia University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently examined cholesterol homeostasis in mice lacking functional peroxisomes (PEX2 Ϫ/Ϫ mice), and demonstrated that: 1) PEX2 Ϫ/Ϫ mice had significantly decreased total cholesterol and high density lipoprotein (HDL) cholesterol levels in plasma; 2) the steady-state cholesterol content in PEX2 Ϫ/Ϫ liver was decreased by 40% relative to control mouse liver; 3) PEX2 Ϫ/Ϫ mice did not lose cholesterol by catabolism to bile acids or excretion in the stool; and 4) PEX2 Ϫ/Ϫ mice failed to maintain normal cholesterol balance, despite a dramatic increase in SREBP-2, its target genes, and cholesterol biosynthesis in most tissues (12).…”
mentioning
confidence: 99%